Log in to add a comment

## Answers

Step 1 Divide all terms by a (the coefficient of x2).

Step 2 Move the number term (c/a) to the right side of the equation.

Step 3 Complete the square on the left side of the equation and balance this by adding the same value to the right side of the equation.

Divide all terms by 2 (the coefficient of x²).

⇒ (2x² - 7x + 3)/2 = 0

⇒ x² - 7x/2 + 3/2 = 0

Move the constant term to the right side of the equation.

⇒ x² - 7x/2 = -3/2

Add the b² term on both sides.

⇒ x² - 2*x*7/4 + (7/4)² = -3/2 + (7/4)² = -3/2 + 49/16

Complete the square on the left side of the equation.

⇒ (x - 7/4)² = (-24+49)/16 = 25/16

⇒ (x-7/4)² = (5/4)²

find the square root.

⇒ x - 7/4 = +- 5/4

⇒ x = 7/4 +- 5/4

⇒ x = 7/4+5/4 and 7/4-5/4

⇒ x = 3 and 1/2